Mathematical models and methods of optimization of technological heating regimes of the piecewise homogeneous glass shell. State-of-the-art investigations - Gachkevich, M. G.; Gachkevich, O. R.; Torskyy, A. R.; Dmytruk, V. A. (Publishing House of Lviv Polytechnic National University, 2015)
In this paper, the state-of-the-art investigations of optimization problems with respect to the stress state of technological heating regimes for piecewise-homogeneous glass shell elements have been analysed, which are important for development of different types of production processes during production of elements of modern devices for specific target application, in particular, vacuum and power equipment. The directions of development of this class of problems of optimization and corresponding approaches to their formulation and solving are identified. Проаналiзовано сучасний стан дослiджень проблеми оптимiзацiї вiдносно напруженого стану режимiв технологiчного нагрiву кусково-однорiдних скляних оболонкових елементiв, важливої для розроблення рiзних рацiональних виробничих процесiв пiд час виготовлення пристроїв конкретного цiльового призначення, зокрема, вакуумного i енергетичного обладнання. Окреслено напрями розвитку такого класу задач оптимiзацiї та вiдповiднi пiдходи до їх формулювання i розв’язування.
Математичнi моделi i методи оптимiзацiї режимiв технологiчного нагрiву скляних кусково-однорiдних оболонок. Стан дослiджень
Keywords: thermal regimes in manufacturing processes; glass piecewise homogeneous shell elements; optimization with respect to stress state